1990
DOI: 10.1042/bst0180549
|View full text |Cite
|
Sign up to set email alerts
|

Reoxygenation of the hypoxic myocardium causes a mitochondrial complex I defect

Abstract: It is well established that reoxygenation of myocardial tissue after a period of hypoxia or ischaemia results in an increase in intracellular calcium [ 11 and the release of cytosolic contents as a consequence of cell lysis 121. As yet the mechanism and sequence of events involved in the so-called 'oxygen paradox' are unresolved. An insight into the mechanism of reoxygenation damage may be gained by investigating those cells which have not sustained lethal damage.Under normal circumstances the energy demands o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
14
0

Year Published

2006
2006
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 0 publications
1
14
0
Order By: Relevance
“…Mitochondria is one of the major organelles that regulates the ROS production, whereas mitochondrial complex I is a main site of ROS production in mitochondria . Substantial evidence is accumulating to suggest that the defect of mitochondrial complex I is a critical determinant of increased mitochondrial ROS generation and subsequent oxidative stress following myocardial I/R injury . Therefore, preventive and therapeutic methods targeting mitochondrial complex I may be more efficient against H/R‐induced oxidative stress.…”
Section: Discussionmentioning
confidence: 99%
“…Mitochondria is one of the major organelles that regulates the ROS production, whereas mitochondrial complex I is a main site of ROS production in mitochondria . Substantial evidence is accumulating to suggest that the defect of mitochondrial complex I is a critical determinant of increased mitochondrial ROS generation and subsequent oxidative stress following myocardial I/R injury . Therefore, preventive and therapeutic methods targeting mitochondrial complex I may be more efficient against H/R‐induced oxidative stress.…”
Section: Discussionmentioning
confidence: 99%
“…ONOO Ϫ -mediated inactivation of complex I increases O 2 ⅐ Ϫ production from that location, and O 2 ⅐ Ϫ generated by complex I is released exclusively into the matrix (16,51,(63)(64)(65). Animal I/RP models showed that, upon RP, the ETC complex activities are reduced, complex I is the main source of mitochondrial ROS (2,31,54), and NO derived from endothelial NOS (eNOS) is the one responsible for ONOO Ϫ formation, inhibition of complex I activity, and suppression of tissue O 2 consumption (84).…”
mentioning
confidence: 99%
“…The hallmarks of cardiac IR injury are found to occur on reperfusion of the myocardium. In terms of the mitochondria, reperfusion injury affects the oxidative phosphorylation (Ox-Phos) pathway, including the ETC, [53][54][55] adenine nucleotide translocase (ANT), 56,57 and Krebs cycle 58,59 enzymes. In addition to Ox-Phos, reperfusion in-jury also leads to cardiolipin oxidation, 55,60,61 the induction of a large proton leak across the mitochondrial inner membrane, 41,62 Ca 2+ overload, overproduction of ROS, PTP opening, and cell death.…”
Section: Mitochondrial Dysfunction In Ir Injurymentioning
confidence: 99%
“…In addition to Ox-Phos, reperfusion in-jury also leads to cardiolipin oxidation, 55,60,61 the induction of a large proton leak across the mitochondrial inner membrane, 41,62 Ca 2+ overload, overproduction of ROS, PTP opening, and cell death. [62][63][64][65][66][67][68][69][70][71][72][73] A majority of these observations have been made in mitochondria isolated from hearts after reperfusion, meaning that the time course of mitochondrial damage during reperfusion injury is difficult to study (because mitochondrial isolation typically takes 1∼2 h).…”
Section: Mitochondrial Dysfunction In Ir Injurymentioning
confidence: 99%